ANGKA KUMAN UDARA DAN LANTAI RUANG RAWAT INAP RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Windi Wulandari; Adi Heru Sutomo; Susi Iravati (Lambung Mangkurat, 2015)
Abstract One of the objectives of health development is a healthy environment including hospital environment. The quality of hospital environment becomes one of that needs to be considered, because of there are some ways of transmission of germ that causing infection could occured through droplet, airborne or direct contact. The spreading of nosocomial infections in hospitals may occur at existing facilities in hospital such as theatre or surgery room, emergency room, outpatient installation, and patient room. To determine the factors those are related to the number of bacteria in the air and floor of inpatient room of PKU Muhammadiyah Hospital Yogyakarta. The study was an observational analytic cross-sectional study design. The populations in this study were all of inpatient rooms at PKU Muhammadiyah Hospital of Yogyakarta. The samples of the observation were all five wards. Data were collected using a check list, measuring temperature, humidity, lighting, number of bacteria in air and floor. Data were analyzed using Pearson correlation test to examine the relationship between variables and using Anova to see the differences. The results showed a significant relationship exists between the number of patients with air bacteria rate (p = 0.037, r = 0.900), there is no correlation between the number of waiters and the number of air bacteria amount (p = 0.505, r = 0.400), there is correlation between the number of visitors and the number of air bacteria (p = 0.037, r = 0.900), there is no correlation between the number of air bacteria of sanitary room (p = 1.000, r = 0.000), there is no correlation betwen the number of patients with floor bacteria rate (p = 0.283, r = -0.602), there is no correlation between the number of waiters with the number of floor bacteria rate (p = 0.420, r = -0.474), there is correlation between the number of visitors to the number of floor bacteria (p = 0.032, r = -0.910), there is no correlation between sanitation floor space with a number of bacteria (p = 0.991, r = -0.007), there is no difference between the number of bacteria by the day (p = 0.82, F = 2.121), there is no difference in the number of floor bacteria by day (p = 0.226). There is a significant correlation between the number of patients and the number of visitors to the average air bacteria rate per week in patient room. The number of patients and the number of visitors are the most powerful variable correlation contributed to the number of bacteria in the air in patient room PKU Muhammadiyah hospital Yogyakarta. Keywords: rate of air bacteria, floor bacteria numbers, inpatient wards, sanitation, hospitals